Answer:
9×5=45
Step-by-step explanation:
hope it helps and use brainly it never lies
Drop out and become a stri pper
Answer:
2 i think
Step-by-step explanation:
An inverse operation is writing the opposite sign to another sign
Answer:
Read explanation
Step-by-step explanation:
Use elimination
Add them all up
y = 1 ( everything else cancels )
-2x + 2(1) + z = 14
3x - 2(1) + z = -5
-x +(1) - 2z = -8
simplify
-2x + z = 12
3x + z = -3
-x -2z = -9
U can't use elimation because it would turn into 0 = 0
change last equation
x + 2z = 9
x = -2z + 9
plug that in
-2(-2z+9) + z = 12
3(-2z+9) + z = -3
-(-2z+9) - 2z = -9
4z - 18 = 12
-6z + 27 + z =-3
2z - 9 - 2z = -9
simplify
4z = 30
-5z = -30
0 = 0
z = 6
y = 1
x = -3